2015
DOI: 10.1098/rsif.2014.1203
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding or restricting defectors in public goods games?

Abstract: When creating a public good, strategies or mechanisms are required to handle defectors. We first show mathematically and numerically that prior agreements with posterior compensations provide a strategic solution that leads to substantial levels of cooperation in the context of public goods games, results that are corroborated by available experimental data. Notwithstanding this success, one cannot, as with other approaches, fully exclude the presence of defectors, raising the question of how they can be dealt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 48 publications
(91 reference statements)
3
56
0
Order By: Relevance
“…We consider here symmetrical games (e.g. the public goods games and their generalizations [24,26,43,40,21]) in which the order of the participants is irrelevant. Let α i0 i1,...,i d−1 be the payoff of the focal player, where i 0 (1 ≤ i 0 ≤ n) is the strategy of the focal player, and i k (with 1 ≤ i k ≤ n and 1 ≤ k ≤ d − 1) be the strategy of the player in position k. These payoffs form a (d − 1)-dimensional payoff matrix [16], which satisfies (because of the game symmetry)…”
Section: Replicator Dynamicsmentioning
confidence: 99%
“…We consider here symmetrical games (e.g. the public goods games and their generalizations [24,26,43,40,21]) in which the order of the participants is irrelevant. Let α i0 i1,...,i d−1 be the payoff of the focal player, where i 0 (1 ≤ i 0 ≤ n) is the strategy of the focal player, and i k (with 1 ≤ i k ≤ n and 1 ≤ k ≤ d − 1) be the strategy of the player in position k. These payoffs form a (d − 1)-dimensional payoff matrix [16], which satisfies (because of the game symmetry)…”
Section: Replicator Dynamicsmentioning
confidence: 99%
“…However, some sort of prior expression of interest on behalf of the agents would be indeed needed in reality for initiating the whole process of reaching semantic agreement. Note that, in our case, non-contributors (i.e., those that do not adopt or advertise partial mappings) are self-restricted from accessing the public good, i.e., they cannot free-ride, because each agent constructs the public good locally through some costly effort, as opposed to the work in [18,20].…”
Section: Related Workmentioning
confidence: 99%
“…The purpose of that work is to discourage various free-riding strategies either by avoiding playing the game with free-riders or by restricting access to the public good for freeriders. As compared to [18,20], we do not consider prior commitment of agents for contributing to the public good, as such a setting often requires monetary transfers among agents. However, some sort of prior expression of interest on behalf of the agents would be indeed needed in reality for initiating the whole process of reaching semantic agreement.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, commitment is one of the most practical tools for maintaining social interactions and takes diverse forms (e.g., from a promise to a deposit and mortgage). Game-theoretical studies have shown that costly commitment can promote the evolution of cooperation in the context of the prisoner's dilemma [4][5][6][7][8]. This widely-studied commitment strategy works in a peer-to-peer fashion by allowing a personal proposer to ask his/her co-player to commit to cooperation, but also enforcing compensation if those who commit defect at a later stage.…”
Section: Introductionmentioning
confidence: 99%